Formulation development and systematic optimization of production fish gelatine nanoparticles as new resource for drug delivery - Subara, Deni; Jaswir, Irwandi; Noorbatcha, Ibrahim Ali; Al-Khatib, Ma'an Fahmi Rashid (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Animal proteins have been chosen as promising material for producing nanoparticle and its applications have become popular on the drug delivery research area. Furthermore, gelatine nanoparticles is best biodegradable material, biocompatible, and chemical modification potential, due to its characteristic, gelatine nanoparticles are very promising in carrier system for drug delivery. Mostly the commercial gelatines are derived from mammalian sources, mainly porcine and bovine. Recently, fish gelatine has provided alternative resources for religious, safety and economic reason. In this present research, the fish gelatine was used as a material for production gelatine nanoparticles. The long-term goal of this study is to develop a nanoparticulate formulation based on halal gelatine, for delivery of fragile molecules such as protein and peptide drug. Fish gelatine nanoparticles were synthesized via a two-step desolvation method. Furthermore, the aim of the present study was to assess various formulation parameters in the first step from two step desolvation method to produce fish gelatine nanoparticles that have minimum in size. In the first step, high molecular weight (HMW) fraction content was optimized by SDS-PAGE. The nanoparticles formed were further characterized for mean size, size distribution using a Zetasizer nano, while the morphology of the particles was evaluated by field emission scanning electron microscope (FESEM). The smallest size of achieved nanoparticles was 227 nm which is suitable for drug delivery. The study indicated that a high fraction of HMW in first step could be obtained with gelatine concentration 9%, temperature 45 °C, centrifugation speed at 9700 rpm, and centrifugation time was 5 minute. The mechanistic of the optimum conditions for producing fish gelatine nanoparticles as well as their characterization are discussed.